Syndrome of Inappropriate Antidiuretic Hormone in Esophageal Cancer Patient - Rahmawati Minhajat; Andi Fachruddin Benyamin; Andi Makbul Aman; Syakib Bakri (Case Reports in Oncological Medicine)
Syndrome of inappropriate antidiuretic hormone (SIADH) is a disorder of fluid and sodium balance characterized by hypotonic hyponatremia, low plasma osmolality, and increased urine osmolality caused by excessive release of antidiuretic hormone (ADH). Malignancy is one of the most common causes of SIADH, but SIADH in esophageal carcinoma is very rarely reported. In this case report, a 74-year-old male patient of moderate differentiation of squamous cell esophageal carcinoma had a recurrent electrolyte balance disorder despite repeated corrections. The patient experienced improvement after fluid restriction and drug administration.